ANTIBACTERIAL EFFECT OF WHITE POMEGRANATE PEEL EXTRACT (PUNICA GRANATUM L) AGAINST STREPTOCOCCUS SANGUINIS - Diniasti, Muthiah; Delima, Anita Rosa; Zakki, Muhamad (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Streptococcus sanguinis is one of the bacteria that plays role in the occurrence of caries, acts as an anchor for the attachment of other oral microorganisms that will form dental plaque in the development of caries. The extract of White Pomegranate peel has several compounds such as flavonoids and tannins that have potential as an antibacterial. Objective: To analyze the antibacterial potency of white pomegranate peel extract against Streptococcus sanguinis bacteria. Methods: Using disc diffusion method (Kirby-Bauer) with 7 treatment groups (n=4). Streptococcus sanguinis bacteria is inoculated in agar medium on petri dish, dripped 50 Î¼l to each disc with 100%, 50%, 25%, 12,5%, 6,25% concentration of pomegranate skin extract, and control group. The petri dish is placed in the incubator at 37oC for 24 hours. Each of antibacterial is observed with the presence of inhibition zones around the disc. The analysis uses Kruskal-Wallis and followed by the Mann-Whitney test. Results: There are inhibitory zones for all treatment concentrations, except for concentration of 12.5%, and 6.25%. There is a significant difference in the concentration of pomegranate skin extract towards the growth of Streptococcus sanguinis bacteria. Conclusion: White pomegranate skin extract has antibacterial potency at 25%, 50%, and 100% concentration